Oubliées de l'histoire officielle. Les femmes du marché Sainte-Anne - Poutanen, Mary Anne; Olson, Sherry (Montréal capitale. L'exceptionnelle histoire du site archéologique du marché Sainte-Anne et du parlement de la province du Canada, 2021)
Keywords: Femmes; Marchés; Sainte-Anne (marché); Travail

Le marché Sainte-Anne au quotidien. Plus insalubre qu'il n'y paraît! - Roy, Christian (Montréal capitale. L'exceptionnelle histoire du site archéologique du marché Sainte-Anne et du parlement de la province du Canada, 2021)
Keywords: Archéologie; Marchés; Sainte-Anne (marché); Égouts

Adrienne Barbier (1652-V. 1721). Pionnière de Montréal et Longueuil - Trudeau, Louise (Histoire Québec, 2020)
Number: 1-2

Roberte Gadois (1628-1716), une femme remarquable - Emery Prud'homme, Robert (Histoire Québec, 2020)
Number: 1-2

Une belle histoire de coopération qui se poursuit - Archambault-Malouin, Diane (Au fil d'ABC / SHAC, Société d'histoire d'Ahuntsic-Cartierville, 2022)
Number: 11
Keywords: Ahuntsic; Arrondissements; Cartierville; Coopérative d'habitation de Montréal; Domaine Saint-Sulpice; La Familiale; Logement; Quartiers

De vieilles filles à célibataires : une enquête d’histoire orale au Québec, 1940 à 1970 - McNeil, Françoise (Université de Sherbrooke, 2020)
Keywords: Femmes; Mariage

Recovering Identities from the Judicial Archives of Quebec - Olson, Sherry; Poutanen, Mary Anne (Histoire sociale / Social History, 2024)
Keywords: Archives; Enfants; Famille; Femmes

Déjouer l’ennui au fort de Ville-Marie à Montréal - Pothier, Louise (Revue d'histoire de la Nouvelle-France, 2023)
issued: 2023-21-00
Keywords: Archéologie; Forts

Les quartiers de la grande bourgeoisie: le cas du Golden Square Mile à Montréal - Bérubé, Harold (Histoire des villes nord-américaines, 2022)
Keywords: Bourgeoisie; Golden Square Mile; Quartiers

Une famille pionnière de la rue Dandurand: celle de George Ineson - Guilbault, Normand; Gaudreau, Guy (Le Bulletin de la Société d'histoire Rosemont-Petite-Patrie, 2021)
Number: 2
Keywords: Famille; Logement; Quartiers; Rosemont

Everyday Life at St Anne's Market. Very, Very Unsanitary! - Roy, Christian (Montréal Capital City. The Remarkable History of the Archaeological Site of St Anne's Market and the Parliament of the Province of Canada, 2022)
Translators: _:n38 Translators: _:n62447
Keywords: Archéologie; Marchés; Sainte-Anne (marché); Égouts

Une histoire sociale de la prostitution: Montréal, 1800-1850 - Poutanen, Mary Anne (Les éditions du remue-ménage, 2021)
Keywords: Femmes; Prostitution

Histoire des communautés noires au Québec et à Montréal (1ère partie) - Tessier, Stéphane (Il était une fois... Montréal-Nord, 2020)
issued: 2020-21-00
Keywords: Esclaves; Noirs

Histoire des communautés noires au Québec et à Montréal (2e partie) - Tessier, Stéphane (Il était une fois... Montréal-Nord, 2020)
issued: 2020-22-00
Keywords: Chemins de fer; Musique; Noirs; Travail

Dans la rue. Une histoire du FRAPRU et des luttes pour le logement au Québec - Saillant, François (Écosociété, 2024)
Keywords: Groupes populaires; Logement

Liens d’amitié, de parenté et d’appartenance à une collectivité : genre, itinérance et aide mutuelle à Montréal au début du XIXe siècle - Poutanen, Mary Anne (Écrire la ville. Pouvoirs, urbanités et modernités dans l’espace québécois (XIXe-XXe siècles), 2023)
Keywords: Femmes; Itinérance

Lueur urbaine : réverbères, émotions et vie nocturne, années 1880 à 1910 - Kenny, Nicolas (Écrire la ville. Pouvoirs, urbanités et modernités dans l’espace québécois (XIXe-XXe siècles), 2023)
Keywords: Rues; Électricité

Les coûts de la vie : genre, citoyenneté et politique des prix à Montréal dans les années 1940 - Fahrni, Magda (Écrire la ville. Pouvoirs, urbanités et modernités dans l’espace québécois (XIXe-XXe siècles), 2023)
Keywords: Alimentation; Femmes; Prix; Épicerie

Les " jeunes ", les " amazones ", les " célestes ": les figures de la panique morale sur les drogues à Montréal dans le journal La Patrie, entre 1921 et 1923 - Grenier, Amélie (Bulletin d'histoire politique, 2020)
issued: 2020-22-00
Keywords: Chinois; Criminalité; Femmes; Patrie (La); Réformistes

Going Together Like a Horse and Carriage: Rentier Marriages and Property Accumulation in Montréal, 1825-1903 - Sweeney, Robert C. H. (Histoire sociale / Social History, 2021)
Number: 112
Keywords: Famille; Logement; Mariage

Le Montréal juif – (2e partie) - Tessier, Stéphane (Il était une fois...Montréal-Nord, 2021)
issued: 2021-24-00
Keywords: Juifs

Three Generations of Goode Family - Breslaw, Caroline (The Westmount Historian, 2021)
Number: 2
Keywords: Famille

Le Montréal juif – (4e partie et fin) - Tessier, Stéphane (Il était une fois...Montréal-Nord, 2022)
issued: 2022-22-00
Keywords: Juifs

La presse gaie au Québec: vecteur d'une communauté - Giguère, Nicholas (Relire les revues québécoises: histoire, formes et pratiques (XXe-XXIe siècle), 2021)
Keywords: Fugues (revue)

The Goode House (The Westmount Historian, 2021)
Number: 2
Keywords: Conservation; Famille; Jardins; Patrimoine

À travers les frontières: la participation de Montréal au réseau d'échange inter-municipal sur les problèmes de logement dans les années 1930 - Racette, Jean-Christophe (Urban History Review / Revue d'histoire urbaine, 2022)
issued: 2022-23-00
Keywords: Logement

La tutelle des enfants mineurs au Bas-Canada: autorité domestique, traditions juridiques et masculinités - Garneau, Jean-Philippe (Revue d'histoire de l'Amérique française, 2021)
issued: 2021-23-00
Keywords: Enfants; Famille; Femmes; Mariage; Veuvage

Eau courante, toilettes à eau et dernières latrines à Montréal, 1856-1915 - Lauzon, Gilles (Revue d'histoire de l'Amérique française, 2020)
issued: 2020-21-00
Keywords: Aqueduc; Égouts

Note de recherche. Les journaliers dans le district de Montréal en 1831 - Dessureault, Christian (Revue d'histoire de l'Amérique française, 2021)
issued: 2021-24-00
Keywords: Famille; Recensements; Travail

Enjeux politiques de la frontière entre salubrité et insalubrité dans l'habitation montréalaise des années 1930 - Racette, Jean-Christophe (Revue d'histoire de l'Amérique française, 2021)
issued: 2021-22-00/2021-23-00
Keywords: Crise; Logement; Pauvreté

Railways and the Urban Soundscape: Montreal, 1850s-1950s - Rudy, Jarrett; Fahrni, Magda; Kenny, Nicolas (Urban History Review / Revue d'histoire urbaine, 2022)
issued: 2022-21-00
Keywords: Chemins de fer; Paysages

Inventories, Interiors, and Women’s Ambitions: Strategies of Property Ownership in Three Mid-19th Century Montreal Public Houses - Poutanen, Mary Anne (Urban History Review/Revue d'histoire urbaine, 2023)
Keywords: Femmes

« Il s'en tuë jusques dans les jardins de Québec ». La place des animaux sauvages dans la ville (Québec et Montréal, 1663-1763) - Riguelle, William (Urban History Review / Revue d'histoire urbaine, 2024)
Keywords: Alimentation; Faune

Sur les traces des immigrants qui se marient dans la vallée du Saint-Laurent pendant la première moitié du XVIIIe siècle - Rompillon-Tran, Samantha (Revue d'histoire de la Nouvelle-France, 2023)
issued: 2023-21-00
Keywords: Français; Mariage

From Conversation to Contract: The Notary's Role in Nineteenth-Century Montreal - Olson, Sherry; Poutanen, Mary Anne (Urban History Review / Revue d'histoire urbaine, 2024)
Keywords: Famille; Notaires

Le Plateau agricole (Bulletin de la Société d'histoire du Plateau-Mont-Royal, 2020)
issued: 2020-24-00
Keywords: Alimentation; Baron (côte à); Côtes; Institut des sourdes-muettes; Jardins; Meunerie; Plateau Mont-Royal

Le Centre de services communautaires du Monastère (CSCM) - Loubert, Huguette (Bulletin de la Société d'histoire du Plateau-Mont-Royal, 2021)
issued: 2021-24-00
Keywords: Groupes populaires

Luttes pour le droit au logement sur le Plateau - Vallée, Bernard (Bulletin de la Société d'histoire du Plateau-Mont-Royal, 2021)
issued: 2021-24-00
Keywords: Crise; Groupes populaires; Logement; Plateau Mont-Royal; Quartiers

La Ligue ouvrière catholique et la naissance de la paroisse Saint-André-Apôtre (première partie) - Ménard, Céline (Au fil d'ABC / SHAC, Société d'histoire d'Ahuntsic-Cartierville, 2022)
Number: 11
Keywords: Ahuntsic; Famille; Jeunesse ouvrière catholique (JOC); Ligue ouvrière catholique; Logement; Quartiers

Chronique d'une maisonnée d'Ahuntsic. La formation d'une institution au cours des années 1920 - Campeau, André (Au fil d'ABC / SHAC, Société d'histoire d'Ahuntsic-Cartierville, 2020)
Number: 7
Keywords: Famille; Mariage

D’abord, prendre en mains son panier d’épicerie - Archambault-Malouin, Diane (Au fil d'ABC / SHAC, Société d'histoire d'Ahuntsic-Cartierville, 2020)
Number: 8
Keywords: Alimentation; Chaurès-Louard; Berthe; La Familiale; Logement; Épicerie

Un territoire à habiter et à aménager (Au fil d'ABC / SHAC, Société d'histoire d'Ahuntsic-Cartierville, 2021)
Number: 9
Keywords: Ahuntsic; Cartierville; Logement; Quartiers; Sault-au-Récollet

Le haut des côtes était la zone. Le nord-est d'Ahuntsic entre 1932 et 1944 - Campeau, André (Au fil d'ABC / SHAC, Société d'histoire d'Ahuntsic-Cartierville, 2021)
Number: 9
Keywords: Ahuntsic; Logement; Pauvreté; Quartiers

Enfin chez soi! - Archambault-Malouin, Diane; Beauchamp, Maurice; St-Marseille, Michel (Au fil d'ABC / SHAC, Société d'histoire d'Ahuntsic-Cartierville, 2021)
Number: 9
Keywords: Coopérative d'habitation de Montréal; La Familiale; Logement; Sault-au-Récollet

Le Comité d’Habitation de Montréal - Ménard, Céline (Au fil d'ABC / SHAC, Société d'histoire d'Ahuntsic-Cartierville, 2022)
Keywords: Ahuntsic; Groupes populaires; Logement

L’implantation des soldats français de la guerre de Sept Ans au Canada (1755-1830) : espace, parcours de vie et intégration sociale - Cousineau, Hubert (Université de Sherbrooke, 2021)
Keywords: Famille; Guerre; Milice

Un double-meurtre à la côte Saint-Joseph : espace et société en milieu périurbain à Montréal au XVIIe-XVIIIe siècle - Martin, Dominic (Université de Sherbrooke, 2023)
Keywords: Famille; Faubourgs

Les Irlandais catholiques de Montréal : genèse d'une communauté, 1800-1834 - Duchesne, Jonathan (Université du Québec à Montréal, 2021)
Keywords: Famille; Irlandais; Mariage

Le discours sur la sexualité, l’alimentation et l’apparence corporelle des adolescentes québécoises durant la décennie 1980 : analyse du magazine Filles d’Aujourd’hui - Dumont-Lévesque, Catherine (Université de Sherbrooke, 2021)
Keywords: Enfants; Femmes

History, Memory, and Struggle in Saint-Henri, Montreal - Burrill, Fred (Université Concordia, 2021)
Keywords: Saint-Henri; Travail

Social Transformation in Notre Dame de Grâce over the Long Sixties - Kastner, Jeffrey (Université McGill, 2023)
Keywords: Centres d'acceuil

Gendered labour, immigration, and deindustrialization in Montreal's garment industry - Laframboise, Lauren (Université Concordia, 2021)
Keywords: Femmes; Grèves; Travail; Vêtements

Jobs, Homes, and the Right to Exist: Neighbourhood Activism in Deindustrializing Toronto and Montreal, 1963-1989 - Vickers, Simon (Université de Toronto, 2021)
Keywords: Quartiers; Travail

Montréal en 1919 : industries, travail et espaces résidentiels - Girard, David (Université du Québec à Montréal, 2020)
Keywords: Tramways; Travail

Una gatta da pelare : vies publiques et vies privées des Italiennes récemment arrivées à Montréal - Vigliano, Chiara (Université de Montréal, 2021)
Keywords: Femmes; Italiens

« Il y a plus de crime à détruire un enfant, qu'à le faire » : traitement communautaire et judiciaire de l'infanticide en Nouvelle-France (1671-1747) - Chasle, Ariane (Université de Montréal, 2022)
Keywords: Criminalité; Enfants; Tribunaux

The Voice of the Child Cries Out Against You: The 1912 Montreal Child Welfare Exhibition in its North American and Transnational Contexts - Vanier, Marie-Hélène (Université Concordia, 2024)
Keywords: Enfants; Exposition; Mortalité

Left Out of the Official History. The Women of St Anne's Market - Poutanen, Mary Anne; Olson, Sherry (Montréal Capital City. The Remarkable History of the Archaeological Site of St Anne's Market and the Parliament of the Province of Canada, 2022)
Translators: _:n62 Translators: _:n62435
Keywords: Femmes; Marchés; Sainte-Anne (marché); Travail

La représentation de la famille dans la peinture figurative nord-américaine durant la première moitié de la guerre froide (1945-1968) : les cas de Fairfield Porter, d'Alex Colville et de Jean Paul Lemieux - Scott, Christophe (Université du Québec à Montréal, 2021)
Keywords: Famille; Peinture

Negotiating Bella Figura: Inside the Childhood Homes of Six Second-Generation Italian-Canadian Women in Montreal - Massa, Lisa (Université Concordia, 2022)
Keywords: Enfants; Femmes; Italiens

Deindustrializing Montreal: Entangled Histories of Race, Residence, and Class - High, Steven C (McGill-Queen's University Press, 2022)
"Point Saint-Charles, a historically white working-class neighbourhood with a strong Irish and French presence, and Little Burgundy, a multiracial neighbourhood that is home to the city's English-speaking Black community, face each other across Montreal's Lachine Canal, once an artery around which work and industry in Montreal were clustered and by which these two communities were formed and divided. Deindustrializing Montreal challenges the deepening divergence of class and race analysis by recognizing the intimate relationship between capitalism, class struggles, and racial inequality. Fundamentally, deindustrialization is a process of physical and social ruination as well as part of a wider political project that leaves working-class communities impoverished and demoralized. The structural violence of capitalism occurs gradually and out of sight, but it doesn't play out the same for everyone. Point Saint-Charles was left to rot until it was revalorized by gentrification, whereas Little Burgundy was torn apart by urban renewal and highway construction. This historical divergence had profound consequences in how urban change has been experienced, understood, and remembered. Drawing extensive interviews, a massive and varied archive of imagery, and original photography by David Lewis into a complex chorus, Steven High brings these communities to life, tracing their history from their earliest years to their decline and their current reality. He extends the analysis of deindustrialization, often focused on single-industry towns, to cities that have seemingly made the post-industrial transition. The urban neighbourhood has never been a settled concept, and its apparent innocence masks considerable contestation, divergence, and change over time. Deindustrializing Montreal thinks critically about locality, revealing how heritage becomes an agent of gentrification, investigating how places like Little Burgundy and the Point acquire race and class identities, and questioning what is preserved and for whom."–
Keywords: Gentrification; Irlandais; Lachine (canal); Noirs; Petite-Bourgogne; Pointe-Saint-Charles; Quartiers; Travail

Grossières indécences: pratiques et identités homosexuelles à Montréal, 1880-1929 - Dagenais, Dominic (McGill-Queen's University Press, 2020)
Keywords: Clubs; Criminalité; Enfants; Police; Quartiers